Guess why people choose international food brands over local food brands? Examining the factors affecting Pakistani consumers in selecting an eating place - Qureshi, Tariq Waheed; Bashir, Shahid; Zeeshan , M.; Mehmood, Sana; Al-Tamimi, Abbod Naseb (International Journal of Psychosocial Rehabilitation, 2020)
Urbanization and transformation has reinterpreted the Pakistani fast-food business and nowadays public has developed a habit of taking meals out of their homes selecting loftier and expedient choices. The consumption of fast-food is becoming popular in youth day-by-day. Escalation in the earnings of the flourishing middle-class has participated to the evolution of fast-food business. Fast-food restaurants have paved momentous inroads into the franchising business of Pakistan. Franchising is seemed as a very direct line to the development and progression of a business. The current research is an effort to study the customers’ ‟perception about their preferences of international food franchise (including McDonalds, Pizza Hut, Burger King, Dominos, Subway and KFC) over local fast food outlets”. This work is based on exploration through primary data collection from 120 regular customers (respondents) living in amain city of Punjab, by using a structured-questionnaire. Plentiful features like quality of food, service, taste, environment, hygiene, health-food, easy takeaway etc. are studied to collect customers’ insight about the selection of fast-food franchise for dining or off-time meals intake. The research exposed that taste and quality of the food items distress the regularity of stopovers to foodstuff openings followed by cleanliness and hygiene. It can set a guideline for business professionals of this business or entrepreneurs who are considering to start fast food business. This study can also be helpful for the local food franchises to flourish their business in parallel to international food chains. Consumer perception of our youth who is a major consumer of such food, can set a bench mark for the fat food sellers to develop certain features in accordance with the liking of the consumers that will lead them to expanded business for them and quality food at affordable prices for the consumers.